1999
DOI: 10.1128/jb.181.10.3193-3200.1999
|View full text |Cite
|
Sign up to set email alerts
|

Replication Mechanism and Sequence Analysis of the Replicon of pAW63, a Conjugative Plasmid from Bacillus thuringiensis

Abstract: A 5.8-kb fragment of the large conjugative plasmid pAW63 fromBacillus thuringiensis subsp. kurstaki HD73 containing all the information for autonomous replication was cloned and sequenced. By deletion analysis, the pAW63 replicon was reduced to a 4.1-kb fragment harboring four open reading frames (ORFs). Rep63A (513 amino acids [aa]), encoded by the largest ORF, displayed strong similarity (40% identity) to the replication proteins from plasmids pAMβ1, pIP501, and pSM19035, indicating that the pAW63 replicon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Previous studies have shown similarity between genes from B. thuringiensis and other bacteria, e.g. enterococci (Wilcks et al 1999;Van der Auwera et al 2005) and Clostridium sp. (Barloy et al 1998), indicating that genes have been shared between B. thuringiensis and indigenous intestinal species.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown similarity between genes from B. thuringiensis and other bacteria, e.g. enterococci (Wilcks et al 1999;Van der Auwera et al 2005) and Clostridium sp. (Barloy et al 1998), indicating that genes have been shared between B. thuringiensis and indigenous intestinal species.…”
Section: Discussionmentioning
confidence: 98%
“…The size of plasmid DNA badly affects electroporation transformation efficiency (Ohse et al 1995;Turgeon et al 2006). Bacillus thuringiensis plasmids consist of two groups: (i) the small plasmids (<15 kb), which perform rolling-circle replication (RC) using a single-stranded intermediate (Andrup et al 2003), and (ii) the large plasmids that normally follow a theta replicating mode with low copy number (Wilcks et al 1999;Huang et al 2006). Large theta replicating plasmids always gave transformation efficiencies lower than those obtained with the small RCR plasmids (Turgeon et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on similarity to other replication proteins identified from plasmids in the B. cereus group and other Gram-positive organisms, the origin of replication was readily identified in pXO2 [101,102]. While well characterized in B. thuringiensis plasmid pAW63, the pXO2 origin of replication was not functionally characterized until recently [80].…”
Section: Theta Repliconsmentioning
confidence: 99%